EGF receptor/Rolled MAP kinase signalling protects cells against activated Armadillo in the Drosophila eye. - Freeman, M; Bienz, M (2001)
beta-catenin/Armadillo are transcriptional co-activators that mediate Wnt signalling in normal development. Activated forms of beta-catenin are oncogenic. We have constructed mutant forms of Drosophila Armadillo which correspond to common human oncogenic mutations, and find them to activate Armadillo constitutively. When expressed in the Drosophila eye, these eventually induce apoptosis in all cell types. Intriguingly, cells in the eye are resistant to the effects of activated Armadillo for a long period prior to the onset of cell death at the mid-pupal stage. This latency is conferred by EGF receptor (EGFR)/MAP kinase signalling, which prevents activated Armadillo from inducing apoptosis; when EGFR signalling naturally ceases, the cells rapidly die. Nemo, the Drosophila homologue of NLK in mice and LIT-1 in Caenorhabditis elegans, does not antagonize activated Armadillo, suggesting that the Nemo-like MAP kinases may not generally interact with Armadillo/beta-catenin. Thus, our results show that activated Armadillo is subject to a specific negative control by EGFR/Rolled MAP kinase signalling.